IMPLIKASI PERBEDAAN QIRAAT DALAM MENETAPKAN ISTINBATH HUKUM PERSPEKTIF ALI ASH-ASHABÛNI DALAM TAFSIR RAWÂ’IUL BAYAN - Nunung Lasmana; Nurrahman, Fahmi (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
In the study of interpretation, the variety of qira'at is one of the sources of interpretation of the Qur'an. When viewed from the aspect of its influence, the differences in qira'at are divided into two, namely those that influence the istinbath of law and those that do not influence the istinbath of law. Therefore, this study aims to provide clarity on the legal implications caused by the differences in qira'at in the Qur'an, especially in QS. Al-Baqarah: 222, QS. An-Nisa: 43, and al-Maidah: 6 according to the perspective of Ali Ash-Shabuni in his tafsir book Rawa'iul Bayan. The research method used is descriptive analytical with a content analysis approach. Based on the results of the study, it can be understood that Ash-Shabuni in interpreting the three verses always presents the differences in qira'at among the scholars of the Qurra' which is then continued with the differences in the istinbath of law according to the scholars of the Islamic school of fiqh, and ends with an opinion that he tarjih argumentatively. Of the three verses, there are three pronunciations that contain differences in qira'at, including يَطْهُرْن can be read as يَطَّهَّرْنَ,  اَوْ لٰامَسْتُمُ  can be read as اَوْ لٰمَسْتُمُ, and وَاَرْجُلَكُمْ can be read as وَاَرْجُلِكُمْ. In the tafsir book Rawa'iul Bayan, it can be understood that the differences in the readings of these three verses have quite significant legal implications in the practice of daily worship.